2018
DOI: 10.1111/1756-185x.13320
|View full text |Cite
|
Sign up to set email alerts
|

Differences in quality of life determinants according to the presence of fibromyalgia in middle‐aged female patients with systemic lupus erythematosus: a multicenter, cross‐sectional, single‐ethnicity cohort

Abstract: Poor sleep quality is the common independent risk factor for poor HRQoL in both middle-aged SLE patients with fibromyalgia and without fibromyalgia. Sleep quality improvement may improve HRQoL in female SLE patients, even in those without fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
2
20
1
Order By: Relevance
“…Thus, SARD patients did not solely meet fibromyalgia criteria based upon their fatigue symptoms, but also had substantial unexplained generalized pain consistent with this diagnosis. These findings are compatible with previous studies that found an increased prevalence of fibromyalgia in SARD patients, either when diagnosed using conventional clinical criteria or the diagnostic criteria used in this study [47–50].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, SARD patients did not solely meet fibromyalgia criteria based upon their fatigue symptoms, but also had substantial unexplained generalized pain consistent with this diagnosis. These findings are compatible with previous studies that found an increased prevalence of fibromyalgia in SARD patients, either when diagnosed using conventional clinical criteria or the diagnostic criteria used in this study [47–50].…”
Section: Discussionsupporting
confidence: 93%
“…A total of 70 unique publications (3,4,10,11, comprised of 27 clinical studies, 16 epidemiologic studies, and 27 studies reporting economic and humanistic burden and unmet need met the inclusion criteria (see Supplementary Appendix C, available at http:// onlinelibrary.wiley.com/doi/10.1002/acr.24431/abstract). Most of the studies were conducted in China (n = 14) (11,19,21,23,28,29,38,43,47,54,59,78,79,82), Japan (n = 13) (31,(33)(34)(35)(36)(37)40,58,65,67,74,75,77), and Taiwan (n = 12) (20,22,24,25,45,52,56,60-62, 64,69), followed by Korea (n = 9) (17,26,32,42,44,53,63,72,76), Australia (n = 7) (4,18,39,49,50,57,…”
Section: Resultsmentioning
confidence: 99%
“…Disease characteristics of patients in included studies. Disease characteristics were reported for SLE patients in studies from Australia (n = 6) (4,18,39,50,57,66), China (n = 15) (11,19,21,23,28,29,38,43,47,54,59,78,79,82), Hong Kong (n = 6) (10,30,46,71,80,81), Japan (n = 13) (31,(33)(34)(35)(36)(37)40,58,65,67,74,75,77), Korea (n = 7) (17,26,41,42,44,63,72), Singapore (n = 4) (27,48,55,70), and Taiwan (n = 10) (20,22,24,25,45,52,…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…Thirdly, we did not have information on concomitant diagnosis of fibromyalgia which is known to impact QOL in SLE patients. 35 Lastly, for the mediation analysis we needed to transform mediator and PRO variables, thus the magnitude of direct and indirect effect could not be easily interpreted. However, the intent of the mediational model analysis was to primarily confirm whether disease activity mediated the relationship between HCQ and PROs.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we did not have information on concomitant diagnosis of fibromyalgia which is known to impact QOL in SLE patients. 35 Lastly, for the mediation analysis we needed to transform mediator and PRO variables, thus the magnitude of direct and indirect effect could not be easily interpreted.…”
Section: Discussionmentioning
confidence: 99%